Highly Active and Coke‐Tolerant Hierarchical Mordenite Catalysts Synthesized by Recrystallization for the Isopropylation of Naphthalene. Issue 18 (4th September 2016) - Lee, Young Hye; Kim, Won Yong; Park, Hunmin; Choi, Yo Han; Lee, Jae Sung
Abstract: In the isopropylation of naphthalene for the production of 2, 6‐naphthalenedicarboxylate, the monomer of polyethylene naphthalate plastic, a shape‐selective mordenite (MOR) zeolite catalyst provides the best selectivity for the desired 2, 6‐diisopropylnaphthalene. However, the small pore size of the zeolite limits the naphthalene conversion and lowers the stability because of pore‐mouth blocking by coke. We discovered that these problems could be mitigated by synthesizing a micro‐meso hierarchical pore structure in the MOR zeolite by the recrystallization of MOR with cetyltrimethylammonium bromide as a mesopore‐forming surfactant. The recrystallized catalysts allow the facile diffusion of bulky molecules through connected meso‐ and micropores to and from active catalytic sites located in the small MOR pores. Relative to microporous MOR, the hierarchical MOR catalyst demonstrated a greatly enhanced activity, stability, and coke tolerance, and the intrinsic high shape selectivity of MOR for 2, 6‐diisopropylnaphthalene was maintained. Mild desilication enlarged the pore volume and formed additional acid sites to increase the activity further. Abstract : MOR, MOR, MOR ! A micro‐meso hierarchical pore structure in a mordenite (MOR) zeolite formed by the recrystallization of MOR demonstrates greatly enhanced activity, stability, and coke tolerance, and the intrinsic high shape selectivity of MOR is maintained.